2007
DOI: 10.1111/j.1365-2710.2007.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists? role in the post-discharge management of patients with heart failure: a literature review

Abstract: This review has demonstrated the effectiveness of pharmacists' interventions to reduce the morbidity and mortality associated with heart failure. However, there is an on-going need for the development and evaluation of pharmacy services for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 37 publications
(74 reference statements)
1
41
0
8
Order By: Relevance
“…Tiltak rettet mot helsevesenet dreier seg om å informere helsepersonell bedre om etterlevelse, å forskrive langtidsvirkende medikamenter (7) og å redusere doseringsfrekvens (7,14). Å involvere farmasøyt har også vist seg å vaere effektivt og anbefales som en del av tverrfaglig oppfølging hos denne pasientgruppen (24).…”
Section: Informasjonunclassified
See 1 more Smart Citation
“…Tiltak rettet mot helsevesenet dreier seg om å informere helsepersonell bedre om etterlevelse, å forskrive langtidsvirkende medikamenter (7) og å redusere doseringsfrekvens (7,14). Å involvere farmasøyt har også vist seg å vaere effektivt og anbefales som en del av tverrfaglig oppfølging hos denne pasientgruppen (24).…”
Section: Informasjonunclassified
“…Det anbefales også at farmasøyt involveres i oppfølgingen av hjertesviktpasienter (24). Dette kan bidra til å øke pasienters kunnskap om medikamenter, sikre optimalisering av behandlingen og redusere fare for bivirkninger (4).…”
Section: Konklusjonunclassified
“…8 Similarly, a retrospective cohort study reviewing the role of a pharmacist in transition to home showed that the odds of readmission within 30 days were reduced by half in the pharmacist follow-up group. 9 More specifically, patients who received assistance from a pharmacist during their transition back to home, including follow-up phone calls, had a readmission rate of 5% compared with 9.5% in the usual care group. 9 The readmission rates in this study were lower than what many others have reported, which suggests that a lower-risk group might have been included as the study population.…”
Section: The "Pro" Sidementioning
confidence: 99%
“…9 More specifically, patients who received assistance from a pharmacist during their transition back to home, including follow-up phone calls, had a readmission rate of 5% compared with 9.5% in the usual care group. 9 The readmission rates in this study were lower than what many others have reported, which suggests that a lower-risk group might have been included as the study population. [1][2][3] As such, it can be postulated that a greater absolute benefit might be seen in a higher-risk population.…”
Section: The "Pro" Sidementioning
confidence: 99%
See 1 more Smart Citation